PENINGKATAN DAYA SAING UMKM/UKM JAWA TENGAH DALAM MENGHADAPI ASEAN ECONOMIC COMMUNITY 2015 - Christy Damayanti, Ryan Ananda Saputra & (Transformasi, 2015)
ASEAN Economic Community (AEC) is a deal that is agreed upon by the ten ASEANcountries in the field of economic cooperation. Such efforts to boost the economy in theSoutheast Asian region. President Susilo Bambang Yudhoyono has signed a PresidentialInstruction No. 6 2014 followed by the issuance of Presidential Decree No. 37 2014 toimprove the competitiveness of the national one in the sector MSME / SME. The aim of thisstudy was to determine how to improve the competitiveness of MSME / SME Central Java inthe face of the AEC. The conclusion of the study increased competitiveness undertaken by thetwo parties, namely through the government's role in the field of capital, licensing,infrastructure, access to technology for MSME / SME, and dissemination of MEA and the roleof MSME / SME itself in improving the quality and quantity of the quality of goods as well asfrom human resources it is still not quite able to face the ASEAN Economic Community 2015.Key words: AEC, Improvement of Competitiveness, MSME / SME Central Java.